Pengaruh Model Learning Cycle Dalam Meningkatkan Keterampilan Menulis Resensi Pada Siswa Kelas XI SMA Negeri Karawang - Sari, Vera Mustika; Huri, Daman; Triyadi, Slamet (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the review writing skills of students taught by the Learning Cycle learning model on student learning outcomes on class XI review materials at SMA Negeri 5 Karawang, to determine the effect of the Learning Cycle learning model on the results of writing reviews for class XI students at SMA Negeri 5 Karawang. This type of research is experimental (quasi experimental) with the research design used is the non-equivalent control group design. The population of this study were all students of class XI and the sample in this study was class XI IPA 6 as the experimental class and XI IPA 7 as the control class. Data processing is done by descriptive statistical analysis and inferential statistical analysis.Based on the results of this study, it can be concluded that the results of writing reviews of students taught by the Learning Cycle model in learning to write reviews for class XI SMA Negeri 5 Karawang are quite good. This can be proven in the tests carried out, namely the posttest test. Where, the posttest results of student learning are included in the high category with an average score of 88.43. There is an effect of using the Learning Cycle learning model on review writing skills on student learning outcomes in class XI SMA Negeri 5 Karawang. This has been proven based on the results of hypothesis testing using the Independent Simple Test, where a significant value is obtained for student learning outcomes, namely 0.000 <0.05.